Interaction of extremophilic archaeal viruses with human and mouse complement system and viral biodistribution in mice. (October 2017) - Wu, Linping; Uldahl, Kristine Buch; Chen, Fangfang; Benasutti, Halli; Logvinski, Deborah; Vu, Vivian; Banda, Nirmal K.; Peng, Xu; Simberg, Dmitri; Moghimi, Seyed Moein
Highlights: Archaeal viruses SMV1 and SSV2 triggers complement activation. Complement activation proceeds through lectin and alternative pathways. MBL/MASPs binds directly to viruses and trigger lectin pathway. C3 opsonization is not vital for viral clearance from the blood. Abstract: Archaeal viruses offer exceptional biophysical properties for modification and exploration of their potential in bionanotechnology, bioengineering and nanotherapeutic developments. However, the interaction of archaeal viruses with elements of the innate immune system has not been explored, which is a necessary prerequisite if their potential for biomedical applications to be realized. Here we show complement activation through lectin (via direct binding of MBL/MASPs) and alternative pathways by two extremophilic archaeal viruses ( Sulfolobus monocaudavirus 1 and Sulfolobus spindle-shaped virus 2) in human serum. We further show some differences in initiation of complement activation pathways between these viruses. Since, Sulfolobus monocaudavirus 1 was capable of directly triggering the alternative pathway, we also demonstrate that the complement regulator factor H has no affinity for the viral surface, but factor H deposition is purely C3-dependent. This suggests that unlike some virulent pathogens Sulfolobus monocaudavirus 1 does not acquire factor H for protection. Complement activation with Sulfolobus monocaudavirus 1 also proceeds in murine sera through MBL-A/C as well as factor D-dependent manner, but C3 deficiency has no overall effect on viral clearance by organs of the reticuloendothelial system on intravenous injection. However, splenic deposition was significantly higher in C3 knockout animals compared with the corresponding wild type mice. We discuss the potential application of these viruses in biomedicine in relation to their complement activating properties.